Endotoxin‐induced changes in expression of cyclooxygenase isoforms in the lamellar tissue of extracorporeally haemoperfused equine limbs. (27th November 2019) - Patan‐Zugaj, Bianca; Egerbacher, Monika; Licka, Theresia F.
Abstract: Angiogenesis and sepsis‐related equine laminitis have several features in common. Both events can be induced by endotoxin (lipopolysaccharide— LPS) and both are associated with increased expression of the enzyme cyclooxygenase (COX), of which two isoforms (COX‐1 and COX‐2) exist. To examine the causal relationship between LPS exposure and COX expression and to investigate the tissue distribution of COX in the LPS‐exposed tissue, the technique of extracorporeal haemoperfusion of isolated equine forelimbs was utilized. Perfusion was performed for 10 hr under physiological conditions (control‐perfused limbs, n = 5) and with addition of 80 ng/L of endotoxin (LPS‐perfused limbs; n = 5). After perfusion, samples of lamellar tissue were collected from the dorsal aspect of the hoof wall. Additional control samples were collected from three non‐perfused limbs. Immunohistochemical analysis was performed using antibodies against COX‐1 and COX‐2, and intensity of immunohistochemical staining was scored for each isoform. In the lamellar tissue of control‐ and LPS‐perfused limbs, there was no significant difference in COX‐1 staining intensity and distribution, whereas COX‐2 expression was significantly increased in LPS‐perfused limbs (especially in endothelial cells, fibroblasts and intravasal leucocytes as well as in epidermal basal cells at the base of the primary epidermal lamellae). These results suggest that COX‐2 and its metabolites are involved in the initiation of pathological changes seen in sepsis‐associated events such as sepsis‐related laminitis. In such cases, COX‐2 could therefore be an important therapeutic target; however, early therapy may be required as increase in COX‐2 expression occurs within 10 hr after LPS exposure.